Implementation of Project Based Learning to Build Entrepreneurial Character in High School Students - Htwe , Thandar; Zaw, Soe Thu; Hlaing, Nandar (Journal of Loomingulisus ja Innovatsioon, 2024)
The development of entrepreneurial character in high school students is essential in preparing them for future challenges in an increasingly dynamic world. Project-Based Learning (PBL) has emerged as an effective pedagogical strategy to foster various skills, including problem-solving, teamwork, and entrepreneurial thinking. However, its application specifically to build entrepreneurial character has not been sufficiently explored in the context of high school education. This study aimed to investigate the effectiveness of Project-Based Learning in enhancing entrepreneurial characteristics such as creativity, risk-taking, leadership, and innovation in high school students. A mixed-method research design was employed, involving both quantitative surveys and qualitative interviews with students and teachers. The results indicated a significant improvement in students’ entrepreneurial skills, particularly in their ability to think critically, take initiative, and collaborate effectively in a team setting. Students also demonstrated greater confidence in pursuing entrepreneurial ventures after participating in PBL activities. The findings suggest that integrating PBL into the curriculum can significantly contribute to the development of entrepreneurial character in high school students, which is essential for fostering future entrepreneurs. This research provides valuable insights for educators and policymakers in rethinking educational practices to better equip students for the challenges of the 21st century.